Immunomorphology and molecular biology of mixed primary liver cancers: is Nestin a marker of intermediate‐cell carcinoma?. Issue 2 (29th October 2019) - Malvi, Deborah; de Biase, Dario; Fittipaldi, Silvia; Grillini, Marco; Visani, Michela; Pession, Annalisa; D'Errico, Antonia; Vasuri, Francesco
Abstract : Aims: Primary mixed liver cancers (PLCs), combined hepatocellular‐cholangiocellular (cHCC‐CC) and intermediate‐cell carcinomas are rare tumours characterised by different molecular mechanisms. Nestin is a marker of progenitor cells with a promising application in human tumours. The aims of the present paper are (i) to determine the expression of Nestin in mixed PLCs; and (ii) to correlate the PLC immunoprofile with the gene expression in each tumour component. Methods and results: We selected 28 mixed PLCs, 13 (46.4%) cHCC‐CC and 15 (53.6%) intermediate‐cell carcinomas. The immunohistochemistry panel consisted of keratin 7, keratin 19, CD56 and Nestin. Next‐generation sequencing analysis was performed on 17 cases (27 specimens) using a multi‐gene custom panel. The differentiated HCC and CC components of cHCC‐CC were negative for Nestin in all cases. The intermediate areas of cHCC‐CC were immunoreactive for Nestin in 92.3% of cases, for CD56 in 76.9% and for K7/K19 in all cases. The immunoprofile of the intermediate‐cell carcinomas showed 73.3% of cases positive for Nestin and 66.7% for CD56. TP53 and TERT were the most frequently mutated genes (31.3% and 17.6% of samples, respectively). Mutations were also found in IDH1, IDH2, PIK3CA and NRAS genes. Intermediate and HCC areas of cHCC‐CC seemed to share the same mutational profile, and both harboured different mutations than the CC component. Conclusions: According to our preliminary data, Nestin was not expressed by hepatocellular or cholangiocellular‐cell components, but was expressed by most of the intermediate cells in PLCs, and therefore could be considered in the differential diagnosis of PLCs, together with mutational profile.